2014
DOI: 10.11648/j.ajce.20140205.11
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study on Comparison of 1D and 2D Seismic Responses of a Basin in Turkey

Abstract: Abstract:Local site conditions such as seismic bedrock depth, bedrock slope of the edge, geometry and characteristics of soil layers, topographical irregularities, etc. are the most important factors affecting earthquake ground motion in a specific site. The amplitude and frequency content of bedrock motion can be changed by local site effects, and this variation is denoted as an amplification or de-amplification. Among the several factors, basin edge effect plays an important role in the transformation of ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A quantitative description of the limits of the 1-D assumption and corresponding predictions of the influence of 2-D and 3-D effects, however, remains a difficult task. While a large number of numerical studies have focused on simulations in idealized 2-D basins with well-known shapes of the sediment-bedrock interface and idealized topographies (e.g., Hisada and Yamamoto 1996, Makra et al 2012, Hasal and Iyisan 2014, Zhu and Thambiratnam 2016, Riga et al 2016, 2018, Zhu et al 2018), only a small number (e.g., Thompson et al 2012, Laurendeau et al 2018) have tried to evaluate the validity of the 1-D assumption and identify the different levels of complexity of site response that should be accounted for. Thompson et al (2012) analyzed 104 arrays in Japan that have recorded surface acceleration higher than 0.3 g and concluded that 16 of these sites resemble the 1-D site response.…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative description of the limits of the 1-D assumption and corresponding predictions of the influence of 2-D and 3-D effects, however, remains a difficult task. While a large number of numerical studies have focused on simulations in idealized 2-D basins with well-known shapes of the sediment-bedrock interface and idealized topographies (e.g., Hisada and Yamamoto 1996, Makra et al 2012, Hasal and Iyisan 2014, Zhu and Thambiratnam 2016, Riga et al 2016, 2018, Zhu et al 2018), only a small number (e.g., Thompson et al 2012, Laurendeau et al 2018) have tried to evaluate the validity of the 1-D assumption and identify the different levels of complexity of site response that should be accounted for. Thompson et al (2012) analyzed 104 arrays in Japan that have recorded surface acceleration higher than 0.3 g and concluded that 16 of these sites resemble the 1-D site response.…”
Section: Introductionmentioning
confidence: 99%
“…(iii) The maps generated by SiSeRHMap may suffer of substantial uncertainties when high complex subsoil features are present. The latter are summarized in the high slope degree of the interfaces (L/H < 8-10 in Hasal and Iyisan, 2014) and in general by sharp variation of the buried morphology. On these effects, it is noted that 1-D seismic response seems to be underperformed mainly at the edge of the valley (Gelagoti et al, 2010).…”
Section: Discussionmentioning
confidence: 99%